Institutional Ethnography: A Tool for Interrogating the Institutional and Political Conditions of Individual Experience - Ursula T. Wright; Tonette S. Rocco (Adult Education Research Conference, 2007)
Institutional ethnography is described and benefits and implications for adult education are discussed.